Morphophysiological and biochemical changes in Enterolobium contortisiliquum seedlings under abiotic stresses - Adriana dos Santos Ferreira; Caio César Pereira Leal; Moadir de Sousa Leite; Clarisse Pereira Benedito; Alek Sandro Dutra; Charline Zaratin Alves; Elis Regina Costa de Morais; Márcio Dias Pereira; Marco Porceddu; Gianluigi Bacchetta; Salvador Barros Torres (Revista Ciência Agronômica, 2023)
ABSTRACT Among the main problems that compromise the development of forest species are water and salt stresses, especially in the early stages of development, when seedlings are more sensitive. Thus, the objective of this study was to evaluate the morphophysiological and biochemical changes in Enterolobium contortisiliquum seedlings subjected to abiotic stresses. The experimental design was randomized complete blocks (RCB), composed of five treatments, with four replicates, and the experimental plot consisted of twenty plants. From the 31st day after sowing, when the seedlings reached approximately 15 cm in height, they began to receive the treatments, which consisted of different levels of electrical conductivity of irrigation water (0.3; 2; 4; 6; 8 dS m-1) for salt stress and periods of water restriction (0; 4; 8; 12 and 16 days without irrigation) for water stress. The traits evaluated were: plant height, root length, stem diameter, number of leaves, leaf area, total dry matter, Dickson quality index, height/shoot dry matter ratio, total soluble sugars, starch, total amino acids and proline. An increase in the electrical conductivity of irrigation water and days without irrigation compromised the development of E. contortisiliquum seedlings, which was intensified from 2 dS m-1 and four days without irrigation for salt and water stresses, respectively. The mechanism of survival of E. contortisiliquum to abiotic stresses involves reduction in the growth and quality of seedlings, with activation of biochemical defense mechanisms of the species.